A comparison study of awareness on risk factors and warning signs of stroke between nursing and medical students in Universiti Sains Malaysia - Yazid, Nurfatihah Mohd (Universiti Sains Malaysia, 2015)
Stroke is a clinical syndrome characterized by rapidly developing signs of focal loss of cerebral function with symptoms lasting more than 24 hours or leading to death. There are some risk factors of stroke which were hypertension, high cholesterol, smoking, and lack of exercise, family history of stroke and poor diet. While the warning signs of stroke are slurred speeches, numbness, weakness, headache, vision problems and shortness of breath. Thus, this study is aimed to compare the awareness level on risk factors and warning signs of stroke between nursing and medical student in USM. Moreover, the researcher also wants to compare the actions taken when someone having a stroke nears them, to compare the sources of information of stroke and lastly to compare the association between selected socio-demographic data (gender and educational entry level) on awareness of risk factors and warning signs of stroke between nursing and medical student in USM. There were 184 respondents included in this study. There was a significant difference in mean level of awareness of risk factors of stroke between nursing and medical students in USM (/?<0.05). The researcher concludes the level of awareness for both programs were good but still need to increase their awareness. Thus, educational program can be conducted to increase the level of awareness of risk factors and warning signs of stroke among nursing and medical students in USM.